Circulating tumor cell number and endocrine therapy index in ER positive metastatic breast cancer patients - Costanza Paoletti (Nature Portfolio, 2021)
Abstract Circulating tumor cells (CTC) are prognostic in metastatic breast cancer (MBC). The CTC-endocrine therapy index (CTC-ETI), consisting of CTC-ER (estrogen receptor), BCL2, human epidermal growth factor receptor (HER2), and Ki67 expression, might predict resistance to endocrine therapy (ET) in patients with ER-positive MBC. One hundred twenty-one patients with ER-positive/HER2-negative MBC initiating a new ET after ≥1 lines of ET were enrolled in a prospective, multi-institutional clinical trial. CTC-ETI and clinical/imaging follow-up were performed at baseline and serial time points. Progression-free survival (PFS) and rapid progression (RP; determined at the 3-month time point) were primary endpoints. Associations with clinical outcomes used logrank and Fisher’s exact tests. At baseline, 36% (38/107) of patients had ≥5 CTC/7.5 ml whole blood (WB). Patients with ≥5 vs. <5 CTC/7.5 ml WB had significantly worse PFS (median 3.3 vs. 5.9 months, P = 0.03). Elevated CTC at 1 month was associated with even worse PFS (1.9 vs. 5.0 months from the 1-month sample, P < 0.001). Low, intermediate, and high CTC-ETI were observed in 71 (66%), 8 (8%), and 28 (26%) patients, with median PFS of 6.9, 8.5, and 2.8 months, respectively (P = 0.008). Patients with high vs. low CTC and CTC-ETI more frequently experienced RP (CTC: 66% vs. 41%; P = 0.03; CTC-ETI: 79% vs. 40%; P = 0.002). In conclusion, CTC enumeration and the CTC-ETI assay are prognostic at baseline and follow-up in patients with ER-positive/HER2-negative MBC starting new ET. CTC at first follow-up might identify a group of patients with ER-positive MBC that could forego ET, but CTC-ETI did not contribute further.